1992
DOI: 10.1161/01.res.71.3.620
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II stimulates two myelin basic protein/microtubule-associated protein 2 kinases in cultured vascular smooth muscle cells.

Abstract: In cultured vascular smooth muscle cells, angiotensin II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
57
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 61 publications
5
57
0
Order By: Relevance
“…VSMCs were isolated from rat thoracic aorta by enzymatic dissociation as described previously [7] and used at passage levels [8][9][10][11][12][13][14][15][16]. Ang II and cytochalasin D were obtained from Sigma (St.Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…VSMCs were isolated from rat thoracic aorta by enzymatic dissociation as described previously [7] and used at passage levels [8][9][10][11][12][13][14][15][16]. Ang II and cytochalasin D were obtained from Sigma (St.Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In past immunoblot experiments with antiphosphotyrosine antibody, Ang II induces tyrosine phosphorylation of proteins with apparent molecular masses of 190, 100-120, 70-80, 45 and 40 kDa in VSMCs [7]. The 45-and 40-kDa proteins have been identified as mitogen-activated protein kinase isozymes [9]. These may be involved in the signaling mechanism from the Ang II receptor to the nucleus and play crucial roles in the growth-promoting action of Ang II.…”
Section: Introductionmentioning
confidence: 99%
“…'.rmal growth factor; NGF, nerve growth factor; PMA, phorboi 12-myristate 13- [14][15][16]. In a preceding report, we have shown that ang II induces tyrosine and serinÂą/threonine phosphorylation and activation of two MAP kinases in cultured VSMC [17]. Thus it is likely that MAP kinases play important roles as intermediates in the signalling pathways from the ang II receptors, as well as the growth factor receptors, to the ribosomes and nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] We have previously reported that in isolated perfused rat aortae, increases in perfusion pressure cause a pressure-dependent increase in the activity of MAPKs.…”
mentioning
confidence: 99%
“…[8][9][10] Angiotensin II and endothelins stimulate MAPKs, leading to stimulation of protein synthesis. [11][12][13][14] We have previously reported that in isolated perfused rat aortae, increases in perfusion pressure cause a pressure-dependent increase in the activity of MAPKs.…”
mentioning
confidence: 99%